Responses of Habitat Quality and Animal Biodiversity to Grazing Activities on the Qinghai-Tibet Plateau - Liu, Yixuan; Liu, Shiliang; Wang, Fangfang; Sun, Yongxiu; Li, Mingqi; Wang, Qingbo; Yu, Lu (Frontiers in Ecology and Evolution, 2021)
Grazing activities perhaps lead to habitat quality degradation and animal biodiversity loss while the effects on the Qinghai-Tibet Plateau (QTP) is still relatively poorly studied. Based on the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) model, geographical detector model and generalized linear mixed model (GLMM), the responses of habitat quality and animal biodiversity to grazing activities at 5 km grid scale were analyzed. Results showed that the overall habitat quality on the QTP was high with 76.43% of the total area, and poor level accounted for19.56%. High level habitat was mainly distributed in the southern part, while the poor level in the northern part. The mean grazing activity explanatory ability to habitat quality, bird species richness and mammal richness were 0.346, 0.430 and 0.354. The interaction effects between slope and grazing activities on habitat quality, bird species richness and mammal richness were the most important interaction effects, and the area affected by the interaction was 73.82%, 46.00% and 46.17% of habitat quality, bird species richness and mammal richness, respectively. The interaction effects on habitat quality, bird species richness and mammal richness all showed “low in the northwest and high in the southeast”. Grazing activities and habitat quality had a positive correlation while bird species richness, and mammal richness negative correlations. The spatial relationship of grazing activities of habitat quality was “higher in the middle and lower around the periphery”, while the spatial distribution of grazing activities of bird species richness and mammal richness was “higher in the east and lower in the west”. This study explicitly revealed the responses of habitat quality and animal biodiversity to grazing activities, thus providing references for biodiversity conservation on the QTP.